Differential gene expression in cells from Fabry and Gaucher diseases: cell reprogramming and culture aging - Amaral, Olga (2020)
Gene expression varies deeply, even in the same individual’s cells, depending on stress factors, cell aging, gene variants or gene and cell manipulation In this work, gene expression can be seen to shift in many genes, using fibroblasts from donors with Fabry and Gaucher type 3 genetic diseases Tests were also made to compare the impact of aging cultures Real time qRT PCR protocols for genes of interest were used for expression comparison after cell induction and reprogramming.